Case Series: Gamma Knife Radiosurgery in Brain Arteriovenous, Is It Good Enough? - Yohan Budi Hartanto; Debora Sharon Rory; Jesisca Jesisca (AKSONA, 2023)
Highlight: Brain AVMs are a special concern due to their inherent high risk of bleeding. Gamma Knife radiosurgery (GKRS), as one of the modality treatments, is intended to induce progressive occlusion of an AVM by using high-dose targeted radiation The result of Gamma Knife radiosurgery (GKRS) can be full obliteration, with complications because adverse radiation effects.   ABSTRACT Introduction: Brain arteriovenous malformations (AVMs) are relatively uncommon. Gamma Knife radiosurgery (GKRS) is one of the AVM’s therapeutic interventions, with both advantages and disadvantages. Here, we report the results of two cases of brain AVM after GKRS. Cases: Case 1: Non-contrast head MRI imaging of a 45-year-old man with persistent left-sided headaches revealed a 1.4 x 2.5 x 2.28 cm AVM nidus in the left parasagittal frontal lobe. After a single GKRS with a 25-Gy marginal dose, the MRI contrast showed complete obliteration, with persistent perifocal edema and headache. Case 2: A 25-year-old woman with a history of generalized seizures. The angiograms revealed an AVM nidus with a diameter of 32.58 mm on her right posterior frontal lobe. After a single GKRS with a 22-Gy marginal dose, the MRI contrast showed full obliteration with large edema. The patient had presented with hemiparesis. Conclusion: In these cases, the results after GKRS were full obliteration with complications of edema, headache, and hemiparesis. We also found that complications appear to be associated with adverse radiation effects.